A low-power nanoelectromechanical (NEM) device with Al-doped HfO2-based ferroelectric capacitor. (January 2021) - Kim, Shinhee; Park, Jae Yeon; Go, Seungwon; Kwon, Hyug Su; Choi, Woo Young; Kim, Sangwan
Highlights: Nano-electro-mechanical (NEM) device with HfO2 -based ferroelectric (FE) has been investigated for low-power operation. The HfO2 -based FE material (HfAlO) is highly compatible to CMOS processes than perovskite materials. The experiment-based theoretical study shows that HfAlO can effectively reduce operating power of NEM device. Abstract: Nanoelectromechanical (NEM) device has been regarded as one of the future switching devices due to its nearly infinite switching slope and zero off-state leakage current. However, it suffers from high pull-in voltage which causes high operation voltage. In this study, a sub-15 nm-thick Al-doped HfO2 -based ferroelectric (FE) layer with a negative capacitance (NC) that can exceed the scalability limitation of the perovskite materials is used for voltage amplification to solve the issue. In detail, the model parameters are extracted from the separately fabricated devices; the capacitor of FE material and the NEM device. Using the parameters, the influences of NC on the NEM device are theoretically examined. In addition, systems with other dopants in HfO2 -based FE material are compared. Finally, the design parameters are optimized for a low-power FE-NEM system.